Very Low Birth Weight Outcomes and Admission Temperature: Does Hyperthermia Matter? - Hannah Brophy; Gaik Min Tan; Charles William Yoxall (Children, 2022)
National and international recommendations for thermal care at preterm birth include recommendations to avoid hypothermia and hyperthermia. There is limited evidence demonstrating harm resulting from admission hyperthermia. Our aim was to assess the relationships between admission temperature and outcomes in very low birth weight (VLBW) babies in a unit with low rates of hypothermia and a higher rate of hyperthermia. This was an observational study based on routinely collected data including demographics, admission temperature, survival and major morbidity outcomes. Subjects were 1104 consecutive inborn VLBW babies admitted to a Neonatal Intensive Care Unit in United Kingdom between 2010 and 2017. Results: 155 (14%) of babies were hypothermic (<36.5 °C) with only 21 (1.9%) < 36 °C, and 254 (23%) of babies were hyperthermic (>37.5 °C). The rate of major abnormality on cranial ultrasound scan was increased in the hyperthermic babies compared to the normothermic babies (37/239 (15.5%) vs. 54/601 (9%), relative risk (95% CI) 1.723 (1.166 to 2.546), p = 0.006). There was no difference in survival or other major morbidity in the hyperthermic babies compared to the normothermic babies. There was no association between hypothermia and survival or any major morbidity, although this probably reflects the low power of the study given the low rates of significant hypothermia. Higher admission temperature was associated with an increase in the risk of major cranial ultrasound abnormality using multiple logistic regression analysis (p = 0.007) with an increased odds ratio (95% CI) of 1.48 (1.11 to 1.97) for each degree of increase. We conclude that admission hyperthermia is independently associated with an increased risk of preterm brain injury. It is not possible to state whether this is a causative association, or whether the association is a consequence of a shared aetiology of perinatal infection.